View of the Vedibandha of the Shiva Temple 1 - Temples of India Project Team (Jio Institute, 2024)
The rear view of Shiva Temple 1 showcases the vedibandha (basal mouldings), incorporating the khura (hoof), the kumbha (pot), the kalasha (a pitcher), and the kapotapalika (cyma recta). The kumbha has intermittent niches housing sculptures of females, couples, and dwarfs. Above the moulding, the jangha (wall) exhibits central projected niches flanked by slightly narrower projected niches.